Physiological release of endogenous tau is stimulated by neuronal activity. (15th February 2013) - Pooler, Amy M; Phillips, Emma C; Lau, Dawn H W; Noble, Wendy; Hanger, Diane P
Abstract : Propagation of tau pathology is linked with progressive neurodegeneration, but the mechanism underlying trans‐synaptic spread of tau is unknown. We show that stimulation of neuronal activity, or AMPA receptor activation, induces tau release from healthy, mature cortical neurons. Notably, phosphorylation of extracellular tau appears reduced in comparison with intracellular tau. We also find that AMPA‐induced release of tau is calcium‐dependent. Blocking pre‐synaptic vesicle release by tetanus toxin and inhibiting neuronal activity with tetrodotoxin both significantly impair AMPA‐mediated tau release. Tau secretion is therefore a regulatable process, dysregulation of which could lead to the spread of tau pathology in disease. Physiological release of endogenous tau is stimulated by neuronal activity: This report provides evidence that stimulation of neuronal activity, or AMPA receptor activation, induces tau release from cortical neurons via a calcium‐dependent mechanism. Dysregulation of this process could lead to the spread of tau pathology in disease.